The Effect of Collaborative Strategic Reading on Grade Six Students’ Reading Achievement - Siti Tamah (IJEE (Indonesian Journal of English Education), 2015)
One of the language skills to master by Indonesian EFL learners is reading. In order to assist learners comprehend reading texts, teachers are challenged to apply various teaching strategies. As this paper focuses on teaching reading, two teaching strategies dealing with reading instruction are compared. To be specific, in this paper the writers conduct a study to find the difference between Collaborative Strategic Reading (CSR) and teacher-centered teaching strategy (by applying skimming and scanning). This study was a quasi experimental, which was conducted upon the sixth graders of an elementary school. The finding showed that reading achievements of the students who are taught using CSR and teacher-centered teaching strategy are not significantly different. Nevertheless, this study using Cohen’s d formula finds that CSR gave a small effect on students’ reading achievement.